Assessing in-season crop nitrogen status based on UAV multispectral imaging and AI-driven model optimization - Yeying Zhou; Syed Tahir Ata-Ul-Karim; Jingru Yin; Marco Canicatti'; Lili Tóth; Sheng Wang; Yuntao Ma; Caicong Wu; Mathias Neumann Andersen; Davide Cammarano (Computers and Electronics in Agriculture, 2026)

Agro-environmental profile of potato cultivation under water and nitrogen managements – A case study in Denmark - Junxiang Peng; Kiril Manevski; Kirsten Kørup; David Parsons; Mathias Neumann Andersen (European Journal of Agronomy, 2026)

Validating the Carnegie-Ames-Stanford Approach for remote sensing of perennial grass net primary production - Shaohui Zhang; Poul Erik Lærke; Mathias Neumann Andersen; Junxiang Peng; Esben Øster Mortensen; Johannes Wilhelmus Maria Pullens; Sheng Wang; Klaus Steenberg Larsen; Davide Cammarano; Uffe Jørgensen; Kiril Manevski (Remote Sensing of Environment, 2025)

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Combining biomass production model with machine learning regression of critical nitrogen concentration for estimating grassland nitrogen requirements - Shaohui Zhang; Poul Erik Lærke; Mathias Neumann Andersen; Esben Øster Mortensen; Kiril Manevski (Computers and Electronics in Agriculture, 2025)

Integrating multi-angle and multi-scale remote sensing for precision nitrogen management in agriculture: A review - Yeying Zhou; Yuntao Ma; Syed Tahir Ata-Ul-Karim; Sheng Wang; Ignacio Ciampitti; Vita Antoniuk; Caicong Wu; Mathias Neumann Andersen; Davide Cammarano (Computers and Electronics in Agriculture, 2025)

Transpiration and water use strategies of three economic tree species in a semi-arid afforestation region - Wenjie Wu; Yue Li; Kiril Manevski; Mathias Neumann Andersen; Bingcheng Si; Yongcai Lou; Hao Feng; Kadambot H. M. Siddique (European Journal of Forest Research, 2025)

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

Tailoring defoliation and nitrogen management for large canopy radiation use and biomass production of perennial systems destined for biorefinery - Shaohui Zhang; Poul Erik Lærke; Mathias Neumann Andersen; Uffe Jørgensen; Kiril Manevski (Agricultural and Forest Meteorology, 2024)

Biochar addition and reduced irrigation modulates leaf morpho-physiology and biological nitrogen fixation in faba bean-ryegrass intercropping - Xuezhi Liu; Weilun Liu; Zhenjuan Su; Junsheng Lu; Peng Zhang; Mengting Cai; Wangcheng Li; Fulai Liu; Mathias Neumann Andersen; Kiril Manevski (Science of The Total Environment, 2024)

Melatonin priming manipulates antioxidant regulation and secondary metabolites production in favour of drought tolerance in Chenopodium quinoa Willd. - Maryam Samadi; Seyed Abdolreza Kazemeini; Fatemeh Razzaghi; Mohsen Edalat; Mathias Neumann Andersen; Sven-Erik Jacobsen; Andrea Mastinu (South African Journal of Botany, 2024)

Accurate estimates of land surface energy fluxes and irrigation requirements from UAV-based thermal and multispectral sensors - Junxiang Peng; Hector Nieto; Mathias Neumann Andersen; Kirsten Kørup; Rene Larsen; Julien Morel; David Parsons; Zhenjiang Zhou; Kiril Manevski (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Nickel toxicity pretreatment attenuates salt stress by activating antioxidative system and ion homeostasis in tomato (Solanum lycopersicon L.): an interplay from mild to severe stress - Muhammad Azeem Subhani; Muhammad Amjad; Muhammad Mohsin Iqbal; Behzad Murtaza; Muhammad Imran; Muhammad Asif Naeem; Ghulam Abbas; Mathias Neumann Andersen (Environmental Geochemistry and Health, 2023)

Elevational shifts in foliar‐soil δ 15 N in the Hengduan Mountains and different potential mechanisms - Qiong Chen; Ji Chen; Mathias Neumann Andersen; Xiaoli Cheng (Global Change Biology, 2022)
The natural abundance of stable nitrogen isotopes (δ 15 N) provides insights into the N dynamics of terrestrial ecosystems, the determination of which is considered an effective approach for gaining a better understanding ecosystem N cycling. However, there is currently little information available regarding the patterns and mechanisms underlying the variation in foliar‐soil δ 15 N among mountain ecosystems. In this study, we examined the determinants of foliar‐soil δ 15 N in association with N transportation rates along an elevational gradient in the Hengduan Mountains. Despite the relatively high levels of available N produced from high N fixation and mineralization, we detected the lowest levels of foliar δ 15 N at 3500 m a.s.l., reflecting the stronger vegetation N limitation at medium high elevations. The enhanced vegetation N limitation was driven by the combined effects of higher microbial immobilization and inherent plant dynamic (the shifts of δ 15 N in vegetation preference, including vegetation community) with changing climate along the elevational gradient. Unexpectedly, we established that soil δ 15 N was characterized by an undulating rise and uncoupled correlation with foliar δ 15 N with increasing elevation, thereby indicating that litter input might not be a prominent driver of soil δ 15 N. Conversely, soil nitrification and denitrification were found to make a more pronounced contribution to the pattern of soil δ 15 N along the elevational gradient. Collectively, our results serve to highlight the importance of microbial immobilization in soil N dynamics and provide novel insights that will contribute to enhancing our understanding of N cycling as indicated by foliar‐soil δ 15 N along elevational gradients.

Does Biochar Particle Size, Application Rate and Irrigation Regime Interact to Affect Soil Water Holding Capacity, Maize Growth and Nutrient Uptake? - Eric Oppong Danso; Francis Monnie; Stephen Abenney-Mickson; Emmanuel Arthur; Edward Benjamin Sabi; Mathias Neumann Andersen (Journal of Soil Science and Plant Nutrition, 2021)

Correction to: Next Generation Sequencing Bulk Segregant Analysis of Potato Support that Differential Flux into the Cholesterol and Stigmasterol Metabolite Pools Is Important for Steroidal Glycoalkaloid Content - Kacper Piotr Kaminski; Kirsten Kørup; Mathias Neumann Andersen; Mads Sønderkær; Mette Sondrup Andersen; Hanne Grethe Kirk; Kåre Lehmann Nielsen (Potato Research, 2018)

Next Generation Sequencing Bulk Segregant Analysis of Potato Support that Differential Flux into the Cholesterol and Stigmasterol Metabolite Pools Is Important for Steroidal Glycoalkaloid Content - Kacper Piotr Kaminski; Kirsten Kørup; Mathias Neumann Andersen; Mads Sønderkær; Mette Sondrup Andersen; Hanne Grethe Kirk; Kåre Lehmann Nielsen (Potato Research, 2016)

Cytosolic glutamine synthetase is important for photosynthetic efficiency and water use efficiency in potato as revealed by high-throughput sequencing QTL analysis - Kacper Piotr Kaminski; Kirsten Kørup; Mathias Neumann Andersen; Mads Sønderkær; Mette Sondrup Andersen; Hanne Grethe Kirk; Kåre Lehmann Nielsen (Theoretical and Applied Genetics, 2015)